Nitric oxide modulates the release of vasopressin from rat hypothalamic explants. - Yasin, S; Costa, A; Trainer, P; Windle, R; Forsling, M; Grossman, A (1993)
The enzyme nitric oxide (NO) synthase is present in the paraventricular nucleus, while nitric oxide has recently been shown to inhibit the stimulated release of corticotrophin-releasing hormone (CRH) in vitro. Thus the possible role of NO in regulating, vasopressin (AVP), which also plays an important role in pituitary-adrenal activity, has been investigated. The effects were studied of the NO donors, L-arginine, syndnonimine-1 (SIN-1) and sodium nitroprusside, on both the basal and stimulated release of AVP, employing a previously validated system. Rat hypothalami were incubated in either medium alone or medium containing the test substances and hormone release was measured by RIA. The effect of L-arginine in the presence of the NO synthase inhibitor, L-NMMA, was also investigated. L-arginine reduced KCl-evoked AVP release; this effect was reversed by L-NMMA and reduced by the addition of ferrous human Hb. Similarly, SIN-1 and sodium nitroprusside attenuated KCl-evoked AVP release. L-arginine also reduced IL-1 beta-stimulated AVP release. NO appears to directly and specifically inhibit the stimulated release of AVP from rat hypothalamic explants in vitro, similar to its effects on CRH. These findings provide further evidence that NO may be involved in neuroendocrine regulation.